FINANCIAL EVALUATION OF SOME AGRICULTURAL INITIATIVE PROJECTS IN IRAQ - & AL-Hiyali, Barbaz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research aims to identify the financial feasibility of some agricultural activities benefiting from the initiative’s lending funds, as well as to show the impact of the agricultural initiative on those projects in terms of raising the financial feasibility of their establishment, in the light of the results of the evaluation criteria addressed in the research. Between the years 2009-2011, the financial accounts of the projects were monitored until 2018 to obtain cash flows for the studied projects. Some projects, despite their high investment costs, have been shown to be able to recover the funds invested in a relatively short period of time, and feed plants and similar projects have the potential to recover their costs in a relatively short period. The index of profitability index also showed that most of the productive activities generate a return that exceeds the dinar invested in close proportions, and loans have a significant role in raising the efficiency and profitability of some projects that the state wishes to revitalize despite the non-profit projects in the natural conditions. The NPV values ​​calculated using a discount factor of 10% in the studied projects were positive, indicating the feasibility of investing in these projects, with the exception of the dairy cattle breeding project, which has a net present value of about -8,730,905 dinars. Results came from the discounted profitability index standard. The project also achieved the largest value of the profitability index, as the value of the index reached about 2.408. The research recommended that the need to use lending funds for the agricultural initiative as a tool to raise the efficiency and feasibility of agricultural projects that would contribute to the process of agricultural development in Iraq.